Adaptation of the closest tree method for a two state quartet to Jukes-Cantor tripod trees - Álvarez González, Ernesto (2023)
We aim to fit 4-state sequences of DNA characters from three species to a tripod tree, whose evolutionary model is Jukes-Cantor. For this purpose, we adapt the closest tree method used in the fit of 2-state sequences coming from four species to a quartet, where the states are purines and pyrimidines and the evolutionary model is CFN. The adaptation requires a multi stage methodology called ‘reduction process’. We take the frequencies of 2-state character patterns on the quartet as parameters and search for solutions to the fit.